Evidence of Combining Pharmacophore Modeling-Docking Simulation for Screening on Neuraminidase Inhibitors Activity of Natural Product Compounds - Muchtaridi1, Muchtaridi; Sy Bing2, Choi; S. Abdurrahim3, Aisyah; A. Wahab2, Habibah (Asian Journal of Chemistry, 2014)
In this study, chemical features of 3D-pharmacophore were built to screen of neuraminidase inhibitors from natural products. The pharmacophore hypothesis selected had five features [one hydrogen bond donor, one negative ionizable (N), one positive ionizable (P) and two hydrophobic moiety (Hy)], also included two excluded volume. The best pharmacophore was created by hypogen in DS 2.5 which has a lowest total cost value (92.055), the highest cost difference (107.807), the lowest RMSD (1.197) and the best correlation coefficient (0.944651). The screening of NADI database natural compounds shows that 167 compounds of 3000 NADI compounds were mapped by using four feature at this screening by optimizing the minimum predicted activity to 0.41. In a docking study, good bonding interaction has been shown by coumarilquinic acid derivatives of NADI compounds mapped against neuraminidase (1FD8B), but only MSC927 has a free energy docking score smaller than DANA-1F8B (-9.56 kcal/mol). We have proved both these methods pharmacophore and docking with the statistic and assay experiment methods. Receiver operating under curve in statistic methods have high value (0.907), whereas MUNANA assay experiment resulted that MSC927 has IC50 smaller than others as mention in silico resulted.